In the garden of beasts : love, terror, and an American family in Hitler's Berlin - Larson, Erik, 1954- (New York : Broadway Paperbacks, 2011)
Documents the efforts of the first American ambassador to Hitler's Germany, William E. Dodd, to acclimate to a residence in an increasingly violent city where he is forced to associate with the Nazis while his daughter pursues a relationship with Gestapochief Rudolf Diels
Das Vorspiel -- The Man Behind the Curtain -- Into the Wood -- House Hunting in the Third Reich -- Lucifer in the Garden -- How the Skeleton Aches -- Disquiet -- Berlin at Dusk -- When Everything Changed -- The Queer Bird in Exile -- "Table Talk."
Includes bibliographical references (pages 423-434) and index
Keywords: Dodd, William E. -- 1869-1940; Diplomats -- United States -- Biography; Historians -- United States -- Biography; National socialism; Germany -- Social conditions -- 1933-1945; Biography